Seasonal distribution of Rickettsia spp. in ticks in northeast Algeria. (January 2019) - Dib, L.; Lafri, I.; Boucheikhchoukh, M.; Dendani, Z.; Bitam, I.; Benakhla, A.
Abstract: This article discusses research conducted on the sampling of two tick species: Ixodes ricinus and Rhipicephalus bursa . Ticks were collected in northern Algeria (El Tarf) in 2014 and studied for differences in abundance and seasonal distribution of population dynamics, as well as tested by PCR for the presence of Rickettsia spp. By molecular tools, four Rickettsia pathogens agents were detected: R. helvetica, R. monacensis, R. raoultii and R. massiliae.